2022
DOI: 10.1002/ijgo.14077
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of conservative treatment of atypical polypoid adenomyoma of the uterus: A two‐center experience

Abstract: Objective Atypical polypoid adenomyoma (APA) is a rare uterine premalignant lesion mainly occurring in premenopausal and nulliparous women. Although hysteroscopic resection (HR) has showed promising results, the conservative management of APA in young women is not standardized, and few data are available in the literature. We aimed to assess oncologic outcomes of the conservative treatment of APA. Methods A multicenter observational retrospective cohort study was performed including all patients with APA who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…( 11 , 21 ) reported that hormonal therapy with medroxyprogesterone acetate is associated with a reduced recurrence rate in patients with APA. In contrast, a multicenter observational retrospective cohort study of 24 patients reported that conservative treatment for APA achieved long-term success in 92.9% of patients who received hysteroscopy alone and 72.3% of patients who underwent hysteroscopy plus progestin ( 14 ), indicating that hysteroscopy is the better treatment approach. Furthermore, a systematic review reported no significant differences between hysteroscopy alone and hysteroscopy with hormone maintenance in terms of the rate of cancer progression (10.8% vs .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…( 11 , 21 ) reported that hormonal therapy with medroxyprogesterone acetate is associated with a reduced recurrence rate in patients with APA. In contrast, a multicenter observational retrospective cohort study of 24 patients reported that conservative treatment for APA achieved long-term success in 92.9% of patients who received hysteroscopy alone and 72.3% of patients who underwent hysteroscopy plus progestin ( 14 ), indicating that hysteroscopy is the better treatment approach. Furthermore, a systematic review reported no significant differences between hysteroscopy alone and hysteroscopy with hormone maintenance in terms of the rate of cancer progression (10.8% vs .…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have demonstrated that progestin therapy after hysteroscopic resection prevents recurrence and the progression to endometrial cancer in patients with APA compared with untreated patients (9-12). In contrast, other studies report that progestin therapy is ineffective (13,14). Third, the impact of concurrent APA on the outcomes of fertility-preserving treatment in patients with EAH and EEC has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…After DL model building, the model should undergo external validation and improvement, with the inclusion of further images and videos from other centers. When a high DL model performance is obtained, the inclusion of cases with other rarer intrauterine pathologies (e.g., Mullerian malformations, atypical polypoid adenomioma, pecoma, sarcoma, trophoblastic disease, retained products of conception) [27][28][29][30] might make the DL model testable in the clinical practice thorough comparison of diagnostic performance by expert endoscopists.…”
Section: Discussionmentioning
confidence: 99%